The Analysis of Ambiguity in Rachel Lippincott’s Novel “Five Feet Apart” - Erlindawaty, Erlindawaty; Kahfi, Muhammad (Lembaga Riset Mutiara Akbar, 2023)
This study deals with the analysis of Ambiguity in Rachel Lippincott’s Novel “ Five Feet Apart” The objectives of this research are to find out the lexical and syntactical ambiguities found in Rachel Lippincott’s Novel “Five Feet Apart”, to find out the most dominant causal factors of ambiguities appeared in Rachel Lippincott’s Novel “Five Feet Apart”, and to describe how the lexical and syntactic ambiguities appeared in Rachel Lippincott’s Novel “Five Feet Apart”. Descriptive qualitative method was used in this study. The data of this study were taken from Rachel Lippincott’s Novel “Five Feet Apart”. There are seven types of lexical ambiguity appeared in the novel. They are Polysemy, Homonymy, Synonym, Hyponymy, Antonym, Redundancy, and Part of speech. Meanwhile there are six types of syntactical ambiguity. They are Personal pronoun, Adjective, Noun, Preposition, Verb and Adverb. Redundancy ambiguity is the most dominant lexical ambiguity and personal pronoun is the most dominant syntactical ambiguity used in this novel. There are two ways how the writer used lexical ambiguity in Rachel Lippincott’s Novel “Five Feet Apart”. First, the writer repeated the words to insist the readers that everything is the same. Second, the writer made sure the readers what the writer described. In syntactical ambiguity, the researcher found that in Rachel Lippincott’s Novel “Five Feet Apart”, the writer often missed the subject pronoun in the novel